2022
DOI: 10.3390/polym14040738
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction of Thermotropic Shape Memory Polymer in Wood for Enhancing Its Dimensional Stability

Abstract: The extension of wood to a wider field has been restrained significantly due to its dimensional instability that arises from variation in moisture content, which in turn brings about the risk of cracking, warping or distortion. This work proposed a novel strategy to stabilize wood by means of the in situ construction of a thermotropic shape memory polymer (SMP) inside wood. The cross-linked copolymer network (PMP) with good shape memory behavior was first investigated based on the reaction of methyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, the shape-memory performance of PFA-modified EP has not been mentioned, and its effect on the properties of bamboo is still unknown. In our previous research, it was found that the dimensional stability of wood was effectively improved by constructing a thermoresponsive shape memory polymer (SMP) inside the wood . The desirable shape recovery ability of the cross-linked copolymer network (PMP) based on MMA and polyethylene glycol diacrylate (PEGDA) was considered to be the main reason for wood dimensional stabilization, as it could counteract the internal stress or retard the shrinkage of cell walls once wood loses water, but the interface interaction between PMP and wood was poor, which would weaken the enhancement effect to some extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the shape-memory performance of PFA-modified EP has not been mentioned, and its effect on the properties of bamboo is still unknown. In our previous research, it was found that the dimensional stability of wood was effectively improved by constructing a thermoresponsive shape memory polymer (SMP) inside the wood . The desirable shape recovery ability of the cross-linked copolymer network (PMP) based on MMA and polyethylene glycol diacrylate (PEGDA) was considered to be the main reason for wood dimensional stabilization, as it could counteract the internal stress or retard the shrinkage of cell walls once wood loses water, but the interface interaction between PMP and wood was poor, which would weaken the enhancement effect to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, it was found that the dimensional stability of wood was effectively improved by constructing a thermoresponsive shape memory polymer (SMP) inside the wood. 25 The desirable shape recovery ability of the cross-linked copolymer network (PMP) based on MMA and polyethylene glycol diacrylate (PEGDA) was considered to be the main reason for wood dimensional stabilization, as it could counteract the internal stress or retard the shrinkage of cell walls once wood loses water, but the interface interaction between PMP and wood was poor, which would weaken the enhancement effect to some extent. Utilizing EP can construct a robust connection between SMP and bamboo, as the epoxy oligomers could react with the hydroxyl group of bamboo as well as form the hydrogen bond between cured EP networks and bamboo components.…”
Section: Introductionmentioning
confidence: 99%
“…In the textile segment, breathable fabrics constituted of SMP offer improved comfort on exposure to varying moisture and temperature. [ 24–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the textile segment, breathable fabrics constituted of SMP offer improved comfort on exposure to varying moisture and temperature. [24][25][26][27][28] Nanoparticulates are usually within the dimensional range of 1-100 nm, behaving as a whole entity relative to transport properties. [29] Additionally, the attributes of nanoparticulates are dimensionally related, changing from those of either fine particulates or bulkish materials.…”
Section: Introductionmentioning
confidence: 99%
“…Furfurylated bamboo obtained by vacuum-pressure impregnation displays high mold resistance [ 13 ]. A crosslinked copolymer network was constructed inside the wood to enhance its dimensional stability and reduce the possibility of cracks, the ASE (anti-swelling efficiency) of modified wood was in the range of 26.98% to 43.77% [ 14 ]. It has been found that impregnation methods and polymer modification can reduce the water-absorbing groups and fill cells effectively, which are considered effective methods to improve hydrophobicity and dimension stability [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%